Inductance effect of passive electromagnetic dampers on building-damper system subjected to near-fault earthquakes. Issue 2 (January 2020) - Guo, Wei; Wu, Xiaoli; Wei, Xinna; Cui, Yao; Bu, Dan
The passive electromagnetic damper was commonly simplified into the linear viscous model in numerical analysis, while this simplification may produce large error when the damper inductance is obvious. In this article, an optimal passive electromagnetic damper with good performance and economy characteristic is proposed by parameter optimization, where the damping density is set as the optimization objective. The hysteresis behavior of the passive electromagnetic damper is verified, and by neglecting the inductance effect, the passive electromagnetic damper can be simplified into the linear viscous model in some cases, but actually the inductance effect is obvious under the high-frequency excitation. Subsequently, the effect of inductance on seismic performance of building damper system under the near-fault earthquake is investigated by comparing the simplified linear viscous model and the accurate passive electromagnetic model. The passive electromagnetic damper was supplemented in a 9-story building, and the analysis of the accurate passive electromagnetic model was carried out by the co-simulation of MATLAB and OpenSees based on the client–server technology. It concludes that the inductance effect is obvious and causes large error when the building damper system is subjected to the near-fault earthquake, and the energy dissipation performance described by the linear viscous model is overestimated.